THE PROFILE OF STUDENTS' CRITICAL THINKING MEASURED THROUGH SCIENCE VIRTUAL TEST ON 9th GRADE IN THE THEME OF LIVING THINGS AND ENVIRONMENTAL SUSTAINABILITY, - Fernandi, R. Auliya Ulul'llmi (2017)
The aims of this study are: (1) to investigate the level students' critical thinking skill on living things and environmental sustainability theme, (2) to examine the critical thinking difference among different gender, learning styles, and students' motivation, and (3) to investigate the correlation between students' critical thinking and students' motivation. This research was conducted due to the importance of critical thinking evaluation or measurement to get current skill description as the basic information to improve critical thinking in junior high school. The method of this study was descriptive research method. 110 students from three junior high school in Kuningan was tested with Science Virtual Test on Living Things and Environmental Sustainability Theme for 9th Grade as the measurement tool of critical thinking based on Inch critical thinking elements, and are given learning style questionnaire and science motivation questionnaire. Generally, the mean scores on six elements and overall critical thinking score from descriptive statistics shows a moderate critical thinking attainments level, with the range 43.33 ≤ score < 69.75, while other two elements shows low critical thinking attainments level (score ≤ 43.33). At significant level 0.05 there is no significant difference between male and female, and also there is no significant difference among visual, aural, read/write, and kinesthetic learning style in critical thinking, while significant difference is founded on three different students' motivation (Low, Moderate, High) groups on four critical thinking element skills. Hence to support the tendency, the correlation test is conducted. The correlation test shows there is no correlation between critical thinking and students' motivation (r = 0.155, p = 0.81). Keywords: critical thinking, science virtual test, students' learning style, students' motivation, Penelitian ini bertujuan untuk: (1) menyelidiki tingkat kemampuan berpikir kritis siswa pada tema makhluk hidup dan kelestarian lingkungan hidup, (2) menyelidiki perbedaan tingkat berpikir kritis antar jenis kelamin, gaya belajar, dan motivasi siwa dalam belajar sains, dan (3) menyelidiki korelasi antara berpikir kritis siswa dan motivasi siswa. Penelitian ini dilakukan karena pentingnya evaluasi berpikir kritis dan pengukuran untuk mendapatkan gambaran berpikir kritis yang jelas sebagai informasi dasar untuk meningkatkan kemampuan berprikir kritis di sekolah menengah pertama. Metode pada penelitian ini adalah metode penelitian deskriptif. 110 siswa yang berasal dari tiga sekolah menengah pertama di Kuningan melakukan tes dengan Science Virtual Test dengan tema makhluk hidup dan kelestarian lingkungan hidup untuk kelas 9 sebagai alat ukur kemampuan berpikir kritis berdasarkan element berpikir kritis Inch, dan diberikan kuesioner gaya belajar dan motivasi sains. Secara umum, skor rata-rata pada enam elemen dan keseluruhan skor berpikir kritis bardasarkan statistik deskriptif menunjukan pencapaian yang sedang, dengan jangkauan 43.33 ≤ skor < 69.75, sementara dua elemen lain menunjukan pencapaian yang rendah (skor ≤ 43.33). Pada taraf signifikansi 0.05, tidak ada perbedaan signifikan antara laki-laki dan perempuan dalam berpikir kritis, juga tidak ada perbedaan yang signifikan antara kelompok gaya belajar visual, aural, read/write, dan kinestetik dalam berpikir kritis. Perbedaan yang signifikan ditemukan pada tiga kelompok motivasi siswa (rendah, sedang, tinggi) dalam empat elemen berpikir kritis. Maka untuk mendukung kecenderungan ini, tes korelasi dilakukan. Tes menunjukan tidak ada hubungan antara berpikir kritis dan motivasi siswa (r = 0.155, p = 0.81). Kata kunci: berpikir kritis, science virtual test, gaya belajar siswa, motivasi siswa,